(3QSGdI aj GdQhMs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf GYde Cf GdTNU GdEfSGfi HXGgQI GdcKja LSO XdeGfi fGbU cGed hJGe RGFd s
(3BNQgG (B:s
(3aGfaPhG dJfNQWhG ai Sdc GdCQhGM GdedchJjI hGdfahS dLHQhJjI Cf JUdhG Edi GdMVQI GdEdgjI dGJfaPhG EdG HSdWGf Ci HMLI HjfI hgj GdJhMjO hGdJLQjO hGdJfhjQ HGdYde hGdYed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdC;eOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs